L’hybridation conceptuelle en question. Le cas du concept de « situation » chez John Dewey et Guy Brousseau - Pierre Gégout (Recherches en Éducation)
This article raises the question of the conceptual consequences of the hybridization in Education and Training Sciences. It argues that such an approach carries the risk of conceptual confusion when the various concepts from very different backgrounds are not sufficiently clarified. Thus, this article takes the example of the concept of "situation" as it is used in Joint Action Theory in Didactics (JATD). It shows that the meaning of this concept is problematic. Indeed, it relates to two very different conceptual systems: the work of Guy Brousseau in didactics, and the philosophical thought of John Dewey. After reminding what the concept of "situation" respectively means in these two systems, we show that they are very different concepts which have only their name in common. In doing so, we plead for greater caution in the hybridization venture that nevertheless characterizes the Education and Training Sciences.